Bio-physical and physiological changes associated with seed enhancement treatments in speciality maize (Zea mays) - MIR, HEENA RASOOL; BASU, SUDIPTA; DADLANI, MALAVIKA; NAGARAJAN, SHANTHA; AGGARWAL, PRAMILA (The Indian Journal of Agricultural Sciences, 2014)
Efficacy of seed enhancement treatments were evaluated on four maize (Zea mays L.) varieties; HQPM-1, VL Amber pop corn, Win orange sweet corn and Navjot. Seeds were subjected to hydropriming (17 h/20°C), halo priming (KNO3: 0.3%/17 h/ 20°C) and magneto priming (1000G/2h) and changes in emergence percentage, its speed, seedling vigour, seedling root growth, seed absorption-desorption patterns and water activity were studied. Seed enhancement treatments significantly increased seedling emergence (23.9-27.7%); speed of emergence (31.1-39.6%); seedling vigour (33.5- 44.5%) and root growth with respect to total surface area, length and volume. These treatments also modified water absorption and desorption patterns of the seed and increased seed water activity compared to control. The most effective treatment was magneto priming, followed by halo and hydro priming. Quality protein maize HQPM 1 showed highest enhancement in different traits among genotypes compared in the study.